The efficacy of Contoya (Lobelia decurrens cav.) in the control of eimeriosis in vivo in rabbits - Reyna-Cotrina, G; Torrel Pajares, T; Rojas-Moncada, J; Vargas Rocha, L (Journal of the Hellenic Veterinary Medical Society, 2024)
The search for alternatives in the control of eimeriosis and the lack of studies on local bioactive plants led to the present research to evaluate the efficacy of Contoya (Lobelia decurrens cav.) under two presentations in the control of Eimeria spp. in rabbits in Cajamarca (Peru). Fifty-six rabbits with a parasite load greater than 400 oocysts per gram of feces were selected and divided into a control group and six treatments of eight replicates. The first three treatment groups were administered in extract presentation and the following three in infusion. The coproparasitoscopic evaluation was performed using the McMaster technique on days 1, 3, and 8 post-dosing. The results showed that both presentations and volumes of Contoya achieve the reduction of parasite load, so this plant can be used in Extract and Infusion of 1 to 3 mL per rabbit indistinctly (p > 0.05). The decrease in efficacy in the days was significant (p < 0. 10), in the treatments with extract a maximum reduction of 99.04% (Day 1) and a minimum of 89.35% (Day 8) was observed. Although, in the group treated with infusion, the maximum reduction of oocysts was achieved (99.62% - Day 1), also in this group the lowest value was obtained (84.96% - Day 8). It is inferred that Lobelia decurrens cav. is effective in controlling eimeriosis in rabbits, both in extract and infusion presentations.